REPRESENTING PSYCHOLOGICAL PROBLEMS IN THE NOVEL “THE PICTURE OF DORIAN GRAY” BY OSCAR WILDE (Ideal Journal of Multidisciplinary Research, 2026)
This article examines the representation of psychological problems in the novel The Picture of Dorian Gray by Oscar Wilde. The study focuses on the inner conflicts of the protagonist, the influence of moral corruption, and the psychological consequences of excessive aestheticism and hedonism. Through literary analysis, the article explores how the author depicts identity crisis, moral disintegration, narcissism, and guilt in the character of Dorian Gray. The research demonstrates that Wilde’s novel not only reflects aesthetic philosophy but also reveals profound psychological tensions associated with human desire, conscience, and moral responsibility.
Keywords: Psychological conflict, aestheticism, moral corruption, narcissism, identity crisis, Victorian literature.